Effect of residual solvent on performance of acrylamide-containing dental materials. Issue 10 (October 2019) - Fugolin, Ana P.; Dobson, Adam; Ferracane, Jack L.; Pfeifer, Carmem S.
Abstract: Objective: Methacrylamide-based monomers are being pursued as novel, hydrolytically stable materials for use in dental adhesives. The impact of residual solvents, due to the chemical synthesis procedures or the need for solvated adhesives systems, on the kinetics of polymerization and mechanical properties was the aim of the present investigation. Methods: Two base monomers (70 wt% BisGMA or HEMAM-BDI — newly synthesized secondary methacrylamide) were combined with 30 wt% N, N-dimethylacrylamide. Eethyl acetate (EtOAc), or 75 vol% ethanol/25 vol% water (EtOH/H2 O) were added as solvents in concentrations of 2, 5, 15 and 20 wt%. The resins were made polymerizable by the addition of 0.2 wt% 2, 2-dimethoxy-2-phenyl acetophenone (DMPA) and 0.4 wt% diphenyliodonium hexafluorophosphate (DPI-PF6). Specimens (n = 3) were photoactivated with a mercury arc lamp (Acticure 4000, 320–500 nm, 250 mW/cm 2 ) for 5 min. Degree of conversion (DC, %) was tracked in near-IR spectroscopy in real time and yield strength and modulus of elasticity were measured in three-point bending after dry and wet storage (n = 6). The data was subject to one-way ANOVA/Tukey's Test (p ≤ 0.05), or Student's t-test (p ≤ 0.001). Results: In all groups for both BisGMA and HEMAM-BDI-based materials, DC and DC at Rpmax increased and maximum rate of polymerization decreased as solvent concentration increased. Despite the increased DC, BisGMA mixtures showed a decrease in FS starting at 5 wt% EtOAc or 15 wt% EtOH/H2 O. Yield strength for the HEMAM-BDI groups was overall lower than that of the BisGMA groups, but the modulus of elasticity was significantly higher. Significance: The presence of residual solvent, from manufacturing or from practitioner's handling, affects polymerization kinetics and mechanical properties of resins. Methacrylates appear to be more strongly influenced than methacrylamides.